Regulation and Banking Performance in Liberalization Context - Zgarni, Amina; Fedhila, Hassouna (International Journal of Economics and Financial Issues, 2018)
The financial liberalization initiated by several countries and always considered beneficial in terms of economic growth has recently shown its negative effects on bank performance. Empirical validation from a sample of ten quoted Tunisian commercial banks, observed over a period stretching from 1990 to 2011, shows that from the date of the total liberalization of the Tunisian financial sector, prudential regulation no longer affects the ROA. Similarly, we noticed that from this same date, the absence of a significant effect of the regulation on the ROE. Finally, the empirical results suggest that, starting from the date of full liberalization, regulatory ratios no longer continue to ensure their role of channeling banking activity and improving bank performance. Keywords: Prudential regulation, Governance, Banking crisis, Banking performance, Financial liberalization. JEL Classifications: G21; G28; F36; E44